Connecting Felda communities with solar electrification during flood disaster : the methodology / Siti Jamiah Tun Jamil, Nur Azfahani Ahmad and Jasrul Jamian Jasiman - Siti Jamiah, Tun Jamil; Nur Azfahani, Ahmad; Jasrul Jamian, Jasiman (Universiti Teknologi MARA, Perak, 2018)
The Malaysian Electricity Supply Industry Outlook 2016 has highlighted that Malaysia’s electricity supply infrastructure is among the best in South East Asia. However, upon flood disaster, the national power supply is easily interrupted and electricity cannot be supplied efficiently to the people, especially for the locals in the rural areas. One of the significant groups affected during flood in the rural areas comes from the FELDA communities. These people are usually left vulnerable in a blackout during flood disaster. Therefore, it is significant to have alternative power supply that can be used as a supporting energy relief during the disaster. One of the potential alternatives energy that can supplement electricity during blackout upon flood disaster comes from solar energy. By using solar energy, electricity can be generated and stored ahead of time at the flood relief center. This flood relief strategies is supported by the National Security Council (KMN) and the Ministry of Rural and Regional Development of Malaysia part of the national flood disaster blue print agenda. Therefore, this research aimed to explore the potential of using solar-generated electricity in helping the FELDA communities in the rural area in facing power disruption during flood disaster. The focus will be on presenting the overview of FELDA flood areas in Malaysia and provide discussion on the research methodology obtained to overcome the issue.